Correlation between MDSC and Immune Tolerance in Transplantation: Cytokines, Pathways and Cell-cell Interaction - Yang, Tianying; Li, Jiawei; Li, Ruimin; Yang, Chunchen; Zhang, Weitao; Qiu, Yue; Yang, Cheng; Rong, Ruiming (Current Gene Therapy, 2019)
MDSCs play an important role in the induction of immune tolerance. Cytokines and chemokines (GM-CSF, IL-6) contributed to the expansion, accumulation of MDSCs, and MDSCs function through iNOS, arginase and PD-L1. MDSCs are recruited and regulated through JAK/STAT, mTOR and Raf/MEK/ERK signaling pathways. MDSCs’ immunosuppressive functions were realized through Tregs-mediated pathways and their direct suppression of immune cells. All of the above contribute to the MDSC-related immune tolerance in transplantation. MDSCs have huge potential in prolonging graft survival and reducing rejection through different ways and many other factors worthy to be further investigated are also introduced.
Keywords: Myeloid-derived suppressor cells